Multi-Objective CMOS-Targeted Evolutionary Hardware for Combinational Digital Circuits - Nedjah, N.; de M. Mourelle, L. (Informatica)
Multi-Objective CMOS-Targeted Evolutionary Hardware for Combinational Digital Circuits